2014
DOI: 10.1159/000360810
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes in Patients with Stroke or Transient Ischemic Attack: Prevalence, Risk and Clinical Management

Abstract: Background: The prevalence of diabetes is emerging worldwide and is an important modifiable risk factor for stroke. People with prediabetes, an intermediate metabolic state between normal glucose metabolism and diabetes, have a tenfold increased risk of developing diabetes compared to those with a normal glucose metabolism. Prediabetes is comprised of impaired fasting glucose and/or impaired glucose tolerance and/or disturbed glycosylated hemoglobin levels. Prediabetes is highly prevalent in nondiabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 64 publications
4
70
0
Order By: Relevance
“…preDM has also been considered as a vascular risk factor for stroke and cardiovascular diseases . The prevalence of preDM in patients with acute ischemic stroke as presented in our study (48.8%) was nearly similar to the findings presented in previous studies (average of 37%) . The prevalence of type 2 diabetes and preDM increased sharply in recent years, especially in Asia .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…preDM has also been considered as a vascular risk factor for stroke and cardiovascular diseases . The prevalence of preDM in patients with acute ischemic stroke as presented in our study (48.8%) was nearly similar to the findings presented in previous studies (average of 37%) . The prevalence of type 2 diabetes and preDM increased sharply in recent years, especially in Asia .…”
Section: Discussionsupporting
confidence: 89%
“…DM and preDM are various stages of abnormal glucose metabolism. Patients diagnosed with preDM are at a relatively high risk for the development of type 2 diabetes in the future . DM is a strong risk factor for acute ischemic stroke .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients who were on clopidogrel had higher prevalence of T2DM and prior stroke, which are associated with worse functional outcome [38][39][40][41][42][43][44] . Therefore, it is possible that clopidogrel might have a beneficial effect on the functional outcome of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Among these factors, abnormal glucose regulation was an established risk factors of recurrent stroke in patients with stroke or TIA. 24 The physiology underlying the elevated risk of recurrent ischemic stroke in diabetic METS may be that it was a recognized risk factor of intracranial atherosclerosis. 25,26 Previous studies also reported that diabetic METS was associated with recurrent ischemic stroke in patients with large-vessel infarction or lacunar stroke, 10,17 which we were not able to examine in our study.…”
Section: Figurementioning
confidence: 99%